Écouter la chanson française de l'oreille droite: l'interprétation sociétale des paroles selon Éric Zemmour - Almeida, José Domingues de (2022)
This article dissects the politically marked reading of the French polemicist and essayist Éric Zemmour of the lyrics of French song for forty years. Zemmour sees in it the reflection of a subtle sociological and socio-cultural mutation of France which, according to him, goes in the direction of decline.